Leading open innovation - Huff, Anne Sigismund; Möslein, Kathrin M.; Reichwald, Ralf, 1943- (MIT Press, 2013)
In today's competitive globalised market, firms are increasingly reaching beyond conventional internal methods of research and development to use ideas developed through processes of open innovation (OI). This book describes the ways that OI expands the space for innovation, describing a range of OI practices, participants, and trends. The contributors report on a variety of OI initiatives, offer theoretical frameworks, and consider new arenas for OI from manufacturing to education.
Keywords: Technological innovations -- Economic aspects.; Diffusion of innovations.; elektronické knihy; electronic books